2013
DOI: 10.1055/s-0040-1703646
|View full text |Cite
|
Sign up to set email alerts
|

DIAGNOSTIC HYSTEROSCOPY IN ABNORMAL UTERINE BLEEDING & IT'S HISTOPATHOLOGIC CORRELATION: OUR EXPERIENCE

Abstract: Aims & objectives: 1) To study the accuracy of hysteroscopy in evaluation of abnormal uterine bleeding in perimenopausal and postmenopausal women. 2) To correlate hysteroscopic findings with histopathologic results. Materials and methods: It is a retrospective study done in the department of OBG at K. S.Hegde Medical Academy, Mangalore. All patients who underwent diagnostic hysteroscopy for abnormal uterine bleeding in the past 6 years were included in this study. Patients underwent clinical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Endometrial cancer is a rare finding in AUB cases with only few studies reporting its prevalence in the range of 1.7-4.1%. 11,12 In present study, on histopathology, 56 (65.11%) cases were shown to have normal/proliferative/atrophic endometrium, 17 (19.76%) had hyperplasia, 3 (3.48%) had calcified endometrium, and 10 (11.62%) had polyp. Similarly, Patil et al 13 also showed the absence of abnormal pathologies in 67% of their patients.…”
Section: Discussionsupporting
confidence: 45%
“…Endometrial cancer is a rare finding in AUB cases with only few studies reporting its prevalence in the range of 1.7-4.1%. 11,12 In present study, on histopathology, 56 (65.11%) cases were shown to have normal/proliferative/atrophic endometrium, 17 (19.76%) had hyperplasia, 3 (3.48%) had calcified endometrium, and 10 (11.62%) had polyp. Similarly, Patil et al 13 also showed the absence of abnormal pathologies in 67% of their patients.…”
Section: Discussionsupporting
confidence: 45%
“…Contrary to findings in present study, Chaudhari and Sathe [17] in their study reported a very high sensitivity and specificity of hysteroscopy for detection of abnormalities (98.3 and 80.5%, respectively). In yet another study, Nandan et al [11] found hysteroscopy to be highly sensitive 92.2% but poorly specific 21.2% in detection of abnormal pathologies when compared to histopathology.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in accordance with the observations of a number of other studies that did not report a single case of endometrial carcinoma in their series. Endometrial cancer is a rare finding in AUB cases with only few studies reporting its prevalence in the range of 1.7-4.1% [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…100% correlation of hysteroscopy and histopathology was noted with simple hyperplasia, Submucousmyoma, Endometrial polyp and cystoglandular hyperplasia. A similar study from Mangalore by Nandan N et al [7] . (2013) also reported correlation between hysteroscopy findings and histopathological examination of endometrial curetting.…”
Section: Discussionmentioning
confidence: 61%